Exercise Addiction in Practitioners of Endurance Sports: A Literature Review - Nogueira, Abel; Molinero, Olga; Salguero, Alfonso; Márquez, Sara (Frontiers in Psychology, 2018)
Practice of endurance sports/activities has gained most devotees over recent decades, thanks to its capacity to maintain and improve health. However, their characteristics and accessibility have facilitated the emergence of addictive behaviours. Excessive practicing can lead to adverse physical and psychological effects seriously prejudicial to health, to the extent that individuals are unable to control this behaviour. Recognizing that exercise addiction is still a controversial concept, the aim of the present review is to analyze the state of research into addictive exercise behaviours, specifically centering on running and endurance sports. To this end, a search covering article written in English and dated from 2010 onward was carried out in the Pubmed, Scopus, Web of Science and EBSCOhost databases. Of a total of 2,675 articles in the four databases, 25 were eligible for the final review. The studies reviewed confirmed that excessive practice could encourage the appearance of addictive behaviours and health problems. Most research has reported no age or sex differences in exercise dependence among endurance sport practitioners; however, obsessive passion and dedication to sports activities may be predictors for addiction to exercise. Owing to terminological confusion and the variety of tools used to measure addiction, figures for prevalence differ widely among studies, with values quoted ranging from 3% to 42%. Furthermore, it is clear that there are problems in delimiting, defining and diagnosing this sort of behaviour, which has led to addiction to exercise not yet being considered a behavioural disorder.